2016
DOI: 10.1378/chest.15-0808
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification of Patients With Acute Symptomatic Pulmonary Embolism Based on Presence or Absence of Lower Extremity DVT

Abstract: word count: 248

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 40 publications
3
62
3
2
Order By: Relevance
“…In contrast, Wicki et al [23] have demonstrated that patients with concomitant DVT have higher risk of death compared to patients without DVT. Furthermore, a recent meta-analysis has indicated that the presence of DVT in patients with acute PE is significantly associated with an increased risk of 30-day mortality [24]. In order to evaluate the clinical significance of DVT in patients with PE, we investigated PE-related clinical composite outcomes and 30-day all-cause mortality in this study and compared PE-related outcome and early mortality between non-DVT group and concomitant DVT group.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Wicki et al [23] have demonstrated that patients with concomitant DVT have higher risk of death compared to patients without DVT. Furthermore, a recent meta-analysis has indicated that the presence of DVT in patients with acute PE is significantly associated with an increased risk of 30-day mortality [24]. In order to evaluate the clinical significance of DVT in patients with PE, we investigated PE-related clinical composite outcomes and 30-day all-cause mortality in this study and compared PE-related outcome and early mortality between non-DVT group and concomitant DVT group.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis, however, should be assessed in prospective clinical trials [44]. By contrast, patients diagnosed with acute symptomatic PE, concomitant DVT was significantly associated with an increased risk of death within 30 days of PE diagnosis [40,45]. In addition, long-term Outcomes after PE (ELOPE) Study indicate that almost half of PE patients can be considered to have a "post-PE syndrome" characterized by exercise limitation at 1 year, which influences their quality of life (QOL) and degree of dyspnea [46].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of concomitant DVT has been identified as an adverse prognostic factor, being independently associated with death within the first 3 months after acute PE [232]. In a meta-analysis investigating 8859 patients with PE, the presence of concomitant DVT was confirmed as a predictor of 30 day all-cause mortality (OR 1.9, 95% CI 1.5-2.4), although it did not predict PE-related adverse outcomes at 90 days [233]. Thus, concomitant DVT can be regarded as an indicator of significant comorbidity in acute PE.…”
Section: Integration Of Aggravating Conditions and Comorbidity Into Rmentioning
confidence: 99%